The effect of simultaneous training on some special physical and physiological variables for soccer players (Journal of the College of Basic Education, 2022)
The effect of simultaneous training on some of the physical, physical and physiological variables of a soccer player.The physiology of sports is one of the basic sciences important to sports workers. As a result of medical advances in physiological research, the researchers were able to obtain physiological information and facts which were clearly interested in the development of training and the codification of training load. The athletic performance at the higher levels requires the use of scientific methods to plan and guide the training process, which provides the coach with real comprehensive information.The researcher believes that the training methods derive their effectiveness from the multiplicity of physiological responses as a result of the effect of the training load and the competition, which is considered a true indicator of the modernization of these methods, as well as the development of the play methods themselves. Despite their multiplicity, they agree on their effects on the functions of the heart, the circulation, and the efficiency of the respiratory system and the rest of the body.He is therefore trying to study the importance of some physical, physiological variables for football players, which are a measure of Egyptian football on a global level.The research aims to identify the impact of using simultaneous training at the level of some physical, physical and physiological variables for football playersIn the light of the objectives and duties of the research, within the limits of the sample and based on the results of the statistical treatment, it was concluded that:- The proposed concurrent training program has resulted in an improvement in the level of some physiological variables in judo players (pulse rate in rest, biocapacity, maximum oxygen consumption, lactic acid during rest) in the experimental research group.- The proposed concurrent training program resulted in improved physical performance of football players in variables (maximum strength - bearing strength - power with speed) of the pilot research group.